Effect of chokeberry (Aronia melanocarpa) extracts on the physicochemical properties of wheat starch pastes and gels stored under refrigerated conditions - Adamczyk, Greta; Pawłowska, Agata Maria; Bobel (Zinchenko), Inna; Szwengiel, Artur; Krystyjan, Magdalena (My University, 2025)
Wheat starch is among the most widely used ingredients in food products. Adding phytochemicals to wheat starch-based foods impacts their properties during processing and influences their quality during storage. This research aimed to investigate the impact of aqueous extract from chokeberry fruits on pasting and textural properties of starch pastes/gels. The extracts from chokeberry with different total extract content (0 and 7 Brix) were obtained and applied at various doses (10, 20, and 30% w/w) as a natural additive to the 5% (w/w) wheat starch suspension. Furthermore, the obtained starch gels with chokeberry extracts were stored for 14 days at 4 C. The pasting characteristic process showed that wheat starch pastes containing chokeberry extracts (0 and 7 Brix) had a higher tendency towards retrogradation. Moreover, the results of the texture analysis confirmed this observation because the hardness values of the wheat starch gels with chokeberry extracts were higher compared to starch gels without the extract (during their 14-day storage). On the other hand, the stability of the gels during storage was also determined by the form of the extract used. The course of changes in hardness values observed during storage indicated that the sugar contained in the extract contributed to smaller fluctuations in these changes. Such observations are important from the point of view of designing starch-based gels that are subjected to storage under refrigerated conditions. Пшеничний крохмаль є одним з найбільш широко використовуваних інгредієнтів у харчових продуктах. Додавання фітохімічних речовин до продуктів на основі пшеничного крохмалю впливає на їхні властивості під час обробки та якість під час зберігання. Метою цього дослідження було вивчення впливу водного екстракту з плодів аронії на пастоподібність та текстурні властивості крохмальних паст/гелів. Екстракти з аронії з різним загальним вмістом екстракту (0 та 7 Брікс) були отримані та застосовані в різних дозах (10, 20 та 30% мас./мас.) як натуральна добавка до 5% (мас./мас.) суспензії пшеничного крохмалю. Крім того, отримані крохмальні гелі з екстрактами аронії зберігалися протягом 14 днів при температурі 4°C. Характеристика процесу пастоподібного процесу показала, що пасти з пшеничного крохмалю, що містять екстракти аронії (0 та 7 Брікс), мали вищу схильність до ретроградації. Більше того, результати аналізу текстури підтвердили це спостереження, оскільки значення твердості гелів з пшеничного крохмалю з екстрактами аронії були вищими порівняно з крохмальними гелями без екстракту (протягом їх 14-денного зберігання). З іншого боку, стабільність гелів під час зберігання також визначалася формою використаного екстракту. Хід змін значень твердості, що спостерігалися під час зберігання, вказував на те, що цукор, що міститься в екстракті, сприяв меншим коливанням цих змін. Такі спостереження важливі з точки зору розробки гелів на основі крохмалю, які підлягають зберіганню в охолоджених умовах.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; горобина чорноплідна; black chokeberry; крохмаль пшеничний; поліфеноли; polyphenols; wheat starch